What Can Explain the Apparent Lack of International Consumption Risk Sharing? - Lewis, Karen K. (Journal of Political Economy, 1996)
Recent research in international business cycles finds that international consumption comovements do not match the risk-sharing predictions of standard complete markets models. In this paper, I ask whether two different types of explanations can help explain this result: (1) nonseparabilities between tradables and nontradable leisure or goods and (2) the effects of capital market restrictions on consumption risk sharing. I find that risk sharing cannot be resolved by either explanation alone. However, when I allow for both nonseparabilities and certain market restrictions, risk sharing among unrestricted countries cannot be rejected. This evidence suggests that a combination of these two effects may be necessary to explain consumption risk sharing across countries.